Ecological Study of Healthcare Childbirth in Indonesia: Does Antenatal Care Matter? - Zulfa Auliyati Agustina; Mara Ipa; Pramita Andarwati; Lusi Kristiana; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2021)
The Indonesian government is encouraging childbirth in healthcare to reduce maternal mortality in Indonesia, which is still high.This study aims to conduct an ecological analysis related to the factors that affect Indonesia’s healthcare childbirth.The researchconducted the ecological analysis using secondary data from the Ministry of Health of the Republic of Indonesia report in 2018. The study takes all provincesas samples. Apart from the proportion of healthcare childbirth, four other variables analyzed as independent variables were the proportion of antenatal care 1st visit, the proportion of antenatal care 4th visit, the ratio of health center per district, and the hospital per 100,000 population ratio. Data were analyzed using a scatter plot.The study results found a tendency for the proportion of healthcare childbirth to be lower in the eastern than other Indonesia regions. The study also found that the higher the antenatal care 1st visit in a province, the higher the proportion of healthcare childbirth in that province.Meanwhile, the higher the antenatal care 4th visit in a region, the higher the proportion of healthcare childbirth in that region. The higher the ratio of health centers per district in a province, the higher the proportion of healthcare childbirth in that province. Moreover, the higher ratio of health centers per district in an area, the higher the proportion of healthcare childbirth in that area.The study concluded that four independent variables were analyzed ecologically related to healthcare childbirthin Indonesia.